Some Functional Equations arising from the Concept of Unexpectedness of an Event in Information Theory - Nath, Prem (Journal of Informatics and Mathematical Sciences, 2011)
The general solutions of some functional equations, without imposing any regularity condition on any one of unknown functions appearing in them, have been obtained.